2018
DOI: 10.1177/2331216518812251
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Effects of Pressure Compensation on TEOAE and DPOAE in Children With Negative Middle Ear Pressure

Abstract: In children with normal cochlear acuity, middle ear fluid often abolishes otoacoustic emissions (OAEs), and negative middle ear pressure (NMEP) reduces them. No convincing evidence of beneficial pressure compensation on distortion product OAE (DPOAE) has yet been presented. Two studies aimed to document effects of NMEP on transient OAE (TEOAE) and DPOAE. In Study 1, TEOAE and DPOAE pass/fail responses were analyzed before and after pressure compensation in 50 consecutive qualifying referrals having NMEP from −… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The DPOAE responses were found to be significantly different at all frequencies tested, with responses for the control group more robust than those in the study group. It has already been found that a history of OME has the effect of lowering DPOAE amplitudes [ 14 , 17 , 21 , 24 , 25 ]. This impairment can cause minor subclinical dysfunction, but in the long term it can lead to irreversible damage to the middle ear or cochlea [ 17 , 21 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The DPOAE responses were found to be significantly different at all frequencies tested, with responses for the control group more robust than those in the study group. It has already been found that a history of OME has the effect of lowering DPOAE amplitudes [ 14 , 17 , 21 , 24 , 25 ]. This impairment can cause minor subclinical dysfunction, but in the long term it can lead to irreversible damage to the middle ear or cochlea [ 17 , 21 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both transient otoacoustic emissions (TEOAEs) and distortion product otoacoustic emissions (DPOAEs) are considered important for the early diagnosis of noise-induced hearing loss [ 18 , 19 ]. Researchers have pointed to decreased DPOAE amplitude due to compromised outer hair cells as a possible cause of hidden hearing loss; moreover, DPOAEs are less affected by natural variations in pressure, compliance, or compensation [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, DPOAEs have shown utility as an objective means of identifying normal and hearing impaired ears, such as for use in newborn hearing screening programs or evaluating other difficult-to-test populations [3][4][5][6], estimating hearing threshold [7][8][9][10], differentiating sensorineural and conductive hearing loss (CHL) [10][11][12], objectively quantifying conductive hearing loss [13][14][15][16], differentiating cochlear and neural pathology for the diagnosis of auditory neuropathy/synaptopathy [17], and monitoring for deleterious side-effects of ototoxic medications [18,19]. Unfortunately, as many otologic conditions prevalent in childhood are characterized by CHL [20][21][22][23] and because CHL can significantly impair interpretation of DPOAE results [24][25][26][27], the full clinical utility of DPOAEs often goes unrealized in pediatric cases. This study was conducted to better define the relationship between CHL magnitude and expected DPOAE amplitude, and in so doing, provide the clinician a basis for moving from a binary 'present' or 'absent' interpretation model to one informed by the systematic impact of CHL on DPOAE findings.…”
Section: Introductionmentioning
confidence: 99%